2019
DOI: 10.1038/s41598-019-47274-6
|View full text |Cite
|
Sign up to set email alerts
|

Chiral spin ordering of electron gas in solids with broken time reversal symmetry

Abstract: In this work we manifest that an electrostatic disorder in conducting systems with broken time reversal symmetry universally leads to a chiral ordering of the electron gas giving rise to skyrmion-like textures in spatial distribution of the electron spin density. We describe a microscopic mechanism underlying the formation of the equilibrium chiral spin textures in two-dimensional systems with spin-orbit interaction and exchange spin splitting. We have obtained analytical expressions for spin-density response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
(78 reference statements)
1
8
0
Order By: Relevance
“…We note that the terms χ t and χ d are generally of the same order of magnitude. Moreover, in case when the electron gas populates both spin subbands µ > Ω 0 /2 the overall response entirely disappears χ t + χ d = 0 (this feature was previously noted by [59,66]). In the opposite case when electrons fill only the lowest spin-subband µ < Ω 0 /2 the terms χ t , χ d have opposite signs, which results in the 𝜉 = 0.6 sign-altering dependence of χ on the Fermi energy.…”
Section: Interplay Between Microscopic Mechanisms and The Role Of Ber...supporting
confidence: 62%
See 3 more Smart Citations
“…We note that the terms χ t and χ d are generally of the same order of magnitude. Moreover, in case when the electron gas populates both spin subbands µ > Ω 0 /2 the overall response entirely disappears χ t + χ d = 0 (this feature was previously noted by [59,66]). In the opposite case when electrons fill only the lowest spin-subband µ < Ω 0 /2 the terms χ t , χ d have opposite signs, which results in the 𝜉 = 0.6 sign-altering dependence of χ on the Fermi energy.…”
Section: Interplay Between Microscopic Mechanisms and The Role Of Ber...supporting
confidence: 62%
“…In the appendix A we present the connection of our method with the wave-packet quasiclassical technique used in [39][40][41]. In the appendix B we relate δs η k , δS η k to the Kubo formula method for the charge-spin correlation functions used in [59]. In particular, we show that the non-adiabatic spin precession is described by the interband correlation functions, while the spin-dipole effect stems from the intraband ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, model calculations indicated that skyrmion-like magnetic Friedel oscillations can be induced by an adatom deposited on a surface characterized by a finite spin-orbit interaction [ 5 ] with a magnetic complexity that is detectable experimentally [ 52 ]. While free electrons scattering at skyrmions could carry a spin-magnetization of chiral nature [ 53 ], topological surface states can trigger interesting physics when eventually hitting a skyrmion [ 54 ].…”
Section: Introductionmentioning
confidence: 99%